Pengaruh Komposisi Limbah Malam Batik terhadap Kualitas dan Emisi Bio-Kokas dari Biochar Baglog Jamur : Bahasa Inggris - Hamim Thohari Mahfudhillah; Siti Azzahra Santika; Adeecha Cinta Islamiah (Casuarina: Jurnal Teknik Lingkungan, 2026)
Batik wax waste and oyster mushroom baglog waste have high potential as raw materials for biomass-based alternative energy. Batik wax waste contains carbon with a calorific value of approximately 42 MJ/kg, while mushroom baglog waste has a high lignocellulose content that functions as a natural adhesive. This study aimed to determine the effect of varying the composition of batik wax waste on the quality and emissions of pyrolyzed mushroom baglog waste-based bio-coke. Mushroom baglog waste was pyrolyzed at 350–400°C for three hours, then mixed with batik wax waste in varying concentrations of 10%, 20%, 30%, 40%, and 50%, with a total mass of 100 grams each. The pressing process was carried out using a Leybold-Heraeus Compact MDP 10-1 machine with a pressure of 2 tons. Bio-coke characterization included proximate tests (moisture content, ash content, volatile matter, and fixed carbon), calorific value using a Parr-6400 Calorimeter, and exhaust emissions using a KOENG KEG-500 Automotive Gas Analyzer. Results showed that increasing the composition of batik wax waste increased the calorific value from 20.37 MJ/kg (P10) to 27.31 MJ/kg (P50). Ash content decreased from 30.2% to 24.88%, while volatile matter increased from 16% to 26.5%. CO and HC emissions decreased significantly, approaching zero at mixtures of ≥20%. Thus, the addition of batik wax waste can improve energy efficiency and reduce pollutant emissions, making pyrolysis-derived bio-coke suitable for development as an environmentally friendly fuel to replace firewood in the small industrial sector.